Composition for geopolymer, geopolymer and preparation method thereof
By using specific compositions and preparation methods, the problems of uneven pore distribution and environmental pollution in the preparation of porous geological polymers are solved, and the lightweight, mechanical strength and efficient thermal insulation performance of the material are improved.
Patent Information
- Application Number
- CN202510399500.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-01
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-04-01
AI Technical Summary
The existing preparation methods of porous geological polymers have problems such as uneven pore distribution, collapse of pore walls and environmental pollution, resulting in unstable material performance and poor insulation effect.
A composite foaming agent, gelling material and water composition with a mass ratio of 1:110-250:40-50 was used to prepare a porous structure geological polymer with excellent thermal insulation properties and mechanical strength through specific foaming treatment and mixing methods.
It achieves the lightweight, mechanical strength and stability of the material, while significantly reducing the thermal conductivity of the material and enhancing its thermal isolation performance.
Smart Images

Figure CN119898998A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of building materials, and in particular to a geopolymer composition, a geopolymer and a preparation method thereof. Background Art
[0002] Geopolymers are a class of inorganic polymers synthesized by alkali-induced reactions. Due to their good physical and chemical properties, such as high strength, high temperature resistance, corrosion resistance and low shrinkage, geopolymers have been used in the construction industry, especially in the fields of concrete, refractory materials and thermal insulation materials. In addition, geopolymers also show certain application potential in environmental engineering, such as wastewater treatment and solid waste harmlessness. Although geopolymers have made certain progress in these traditional applications, their application in some emerging fields is still limited.
[0003] Porous geopolymers can significantly reduce their thermal conductivity by introducing a large number of evenly distributed pores inside the material while maintaining certain mechanical properties. This porous structure makes it possible to reduce the weight of geopolymers, improve their thermal insulation performance, and enhance their sound insulation performance.
[0004] At present, the preparation methods of porous geopolymers mainly include the introduction of foaming agents, pore-forming agents or the use of template burn-off method. However, these methods often have the following problems: first, the pore distribution is uneven, resulting in unstable material performance; second, the pore wall collapse is prone to occur during the preparation process, affecting the overall thermal insulation effect; third, some pore-forming agents may cause environmental pollution, which does not meet the requirements of green development.
[0005] Therefore, how to obtain porous geopolymers with high thermal insulation performance by optimizing the preparation process while maintaining the good mechanical properties of geopolymers has become a key issue in current research and application.
[0006] CN102617106A discloses a mineral polymer foam material, which comprises the following components by weight: 50-100 parts of metakaolin, 0-50 parts of admixture, 50-100 parts of water glass, 0.1-15 parts of foaming agent, 0-10 parts of foam stabilizer and 10-90 parts of water. However, the scheme has a complex ratio of the multi-component system, resulting in insufficient controllability of the preparation process, and the lightness and strength matching of the prepared sample are insufficient (for example, the compressive strength is only 0.8MPa when the density is 320 kg / m³), resulting in insufficient practicality of the material.
[0007] Therefore, it is of great significance to invent a porous structure geopolymer with high thermal insulation performance. Summary of the invention
[0008] The purpose of the invention is to overcome the problems of poor thermal insulation performance and insufficient lightness of geopolymer materials.
[0009] In order to achieve the above-mentioned object, the first aspect of the present invention provides a geopolymer composition, which contains a composite foaming agent, a gelling material and water in a mass ratio of 1:110-250:40-50; The composite foaming agent contains a foaming agent, sodium dodecyl sulfate and sodium dodecyl sulfonate in a mass ratio of 10:0.5-2:0.5-2; the pH value of the foaming agent is ≥8; the gelling material contains an alkali activator and an admixture in a mass ratio of 1:10-13; The modulus of the alkali activator is 1-1.2; and the admixture contains metakaolin and slag.
[0010] The second aspect of the present invention provides a method for preparing a geopolymer, which is carried out using the composition for geopolymers described in the first aspect, and the method comprises: (1) subjecting a composite foaming agent to foaming treatment with water to obtain foam; and, The gelling material and water are first mixed to obtain a solution 1; (2) The foam and the solution 1 are mixed for a second time to obtain the geopolymer.
[0011] The third aspect of the present invention provides a geopolymer, which is prepared by the method described in the second aspect.
[0012] The present invention has at least the following advantages: (1) The geopolymer of the present invention not only realizes the lightweight of the material, but also has excellent mechanical strength and stability.
[0013] (2) The geopolymer of the present invention has low thermal conductivity, which effectively enhances the thermal insulation performance of the material.
[0014] (3) The process for preparing geopolymers in the present invention is simple and has low energy consumption, and has excellent application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 is a scanning electron microscope image of the geopolymer prepared in Example 6; Figure 2 is a computed tomography (CT) image of the geopolymer prepared in Example 6. DETAILED DESCRIPTION
[0016] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0017] It should be noted that, in various aspects of the present invention, for the same components or terms in various aspects, the present invention is described only once in one aspect without repeated description, which should not be understood by those skilled in the art as a limitation of the present invention.
[0018] As mentioned above, the first aspect of the present invention provides a geopolymer composition, which contains a composite foaming agent, a gelling material and water in a mass ratio of 1:110-250:40-50; The composite foaming agent contains a foaming agent, sodium dodecyl sulfate and sodium dodecyl sulfonate in a mass ratio of 10:0.5-2:0.5-2; the pH value of the foaming agent is ≥8; the gelling material contains an alkali activator and an admixture in a mass ratio of 1:10-13; The modulus of the alkali activator is 1-1.2; and the admixture contains metakaolin and slag.
[0019] In the technical solution of the present invention, a composite foaming agent of specific components is used, and a specific gelling material including an alkali activator with a modulus of 1-1.2, metakaolin and slag is used, so that the prepared geopolymer has excellent thermal insulation performance and mechanical strength, while maintaining the lightweight characteristics of the material, and is suitable for high-temperature thermal insulation materials in the fields of construction, energy conservation and aviation, and provides an excellent solution for engineering applications in high-temperature environments.
[0020] Preferably, the mass ratio of the composite foaming agent, the gelling material and the water is 1:120-150:40-50.
[0021] Preferably, the foaming agent is selected from Enlin 12# and or HZ-1.
[0022] It should be noted that Enlin 12# and HZ-1 are models of foaming agents. Enlin 12# was purchased from Hebei Enlin Building Materials Co., Ltd., and HZ-1 was purchased from Jiangsu Subote New Materials Co., Ltd.
[0023] More preferably, the foaming agent is Enlin 12#. The geopolymer prepared by using the foaming agent in combination with the other components of the present invention has better thermal insulation and mechanical properties.
[0024] Preferably, the alkaline activator is a combination of potassium silicate and potassium hydroxide.
[0025] It should be noted that the modulus of the alkaline activator refers to the modulus of silicon dioxide (SiO 2 ) and the total number of moles of alkali metal oxides (K 2 O), wherein silicon dioxide and alkali metal oxides are obtained by converting the actual components of the raw materials into chemical equivalents.
[0026] Preferably, the metakaolin accounts for 70-95% of the total mass of the admixture, and the slag accounts for 5-30% of the total mass of the admixture. Under this preferred condition, it helps to significantly improve the foaming stability and final pore structure of the mineral polymer foam material, and can improve the strength and rigidity of the material while maintaining its light weight and good thermal insulation and sound insulation properties. The active ingredients in the slag can synergize with the components of the metakaolin, effectively control the expansion of the foaming agent during the foaming process, reduce the amount of foaming agent used, and make the foamed material have stronger anti-permeability and durability.
[0027] Preferably, the admixture is a combination of metakaolin and slag.
[0028] Preferably, the slag in the present invention is slag that meets the GB / T 18046-2017 standard.
[0029] As mentioned above, the second aspect of the present invention provides a method for preparing a geopolymer, which is carried out using the geopolymer composition described in the first aspect, and the method comprises: (1) subjecting a composite foaming agent to foaming treatment with water to obtain foam; and, The gelling material and water are first mixed to obtain a solution 1; (2) The foam and the solution 1 are mixed for a second time to obtain the geopolymer.
[0030] In the present invention, by controlling the order of adding different raw materials, the different admixtures are mixed more evenly, ensuring that the geopolymer exhibits better mechanical properties and thermal insulation properties on the basis of light weight; in addition, by foaming the composite foaming agent and then performing the second mixing with the solution 1, the pore structure and uniformity of the foaming material can be further optimized. The foam reacts fully with the active ingredients in the solution 1, which can effectively adjust the stability of the foaming agent and ensure uniform distribution of the pores. Through this process, not only the foaming effect is improved, but also the mechanical properties and thermal stability of the foaming material are enhanced.
[0031] It should be noted that the present invention has no particular limitation on the operation or equipment used for the foaming process, as long as a uniform creamy foam can be obtained. Those skilled in the art can make a selection based on technical means known in the art, and the present invention will not go into details herein, and those skilled in the art should not interpret this as a limitation on the present invention.
[0032] Preferably, in the foaming process of step (1), the mass ratio of the composite foaming agent to the water is 1:10-20. When the foam prepared under this specific condition in the present invention is used to prepare geopolymer, the thermal insulation performance of the material is effectively enhanced, and at the same time, it is more conducive to the lightweight of the material.
[0033] Preferably, in step (1), the foaming treatment operation includes: the foaming temperature is 30-40° C., and the time is 2-5 min.
[0034] Preferably, the first mixing and the second mixing independently meet the following conditions: temperature is 20-40° C., time is 2-30 min, and stirring speed is 500-1000 rpm.
[0035] According to another preferred embodiment, the product obtained by the mixing process is sequentially subjected to injection molding and curing processes to obtain the geopolymer.
[0036] Preferably, the curing treatment conditions include: temperature of 60-80°C, time of 48-60h, and relative humidity of 85-95%.
[0037] The present invention has no particular limitation on the operation of the injection molding, and those skilled in the art can make their own selections based on technical means known in the art. The present invention exemplifies a preferred specific implementation method in the following text, which will not be described in detail here, and those skilled in the art should not interpret it as a limitation on the present invention.
[0038] As mentioned above, the third aspect of the present invention provides a geopolymer, which is prepared by the method described in the second aspect.
[0039] In the following examples, unless otherwise specified, the raw materials are all common commercially available products.
[0040] Potassium silicate: K 2 SiO 3 , CAS No.: 1312-76-1, purchased from Sinopharm Chemical Reagent Co., Ltd.
[0041] Foaming agent Enlin 12#: Model: 12#, pH 10, purchased from Hebei Enlin Building Materials Company.
[0042] Foaming agent 1: Model: HZ-1, pH 10.5, purchased from Jiangsu Subote New Materials Co., Ltd.
[0043] Foaming agent 2: Enlin 85#, model: 85#, pH 7.2, purchased from Hebei Enlin Building Materials Company.
[0044] Example 1 (1) 3.18 g of a composite foaming agent (the mass ratio of the foaming agent Enlin 12#, sodium dodecyl sulfate and sodium dodecyl sulfonate is 10:1:1) and 31.8 g of water are subjected to foaming treatment to obtain foam; the foaming treatment conditions are: temperature 40°C, time 5 min; the mass ratio of the composite foaming agent to water is 1:10; (2) 34 g of an alkali activator (potassium silicate and potassium hydroxide) having a modulus of 1.1, 350 g of an admixture (the mass ratio of metakaolin to slag is 95:5) and water are mixed for the first time to obtain a solution 1; the conditions for the first mixing are: a temperature of 20° C., a time of 3 min, and a stirring speed of 750 rpm; The mass ratio of the composite foaming agent, the gelling material and the total amount of added water (the water added in step 1 and step 2) is 1:120.7:45.54; the mass ratio of the alkali activator and the admixture is 1:10.29; (3) performing a second mixing of the foam in step (2) and solution 1 to obtain a geopolymer slurry having a creamy texture; the second mixing conditions are: first stirring at 150 rpm for 2 min, then stirring at 750 rpm for 30 s, and the temperature is 20° C.; (4) The geopolymer slurry was quickly poured into a triple steel mold with a size of 4 cm × 4 cm × 16 cm and sealed and molded. The mold was demolded after 24 hours. The demolded product was then placed in a steam curing box at 60°C for 48 hours (relative humidity of 90%) to obtain a geopolymer.
[0045] Example 2 This example adopts the same process as Example 1, except that: in this example, while keeping the total amount of 350g of admixture unchanged, the mass ratio of kaolin to slag is 90:10, and the rest is the same as Example 1 to prepare a geopolymer.
[0046] Example 3 This example adopts the same process as Example 1, except that, in this example, the mass ratio of kaolin to slag is 85:15 while keeping the total amount of admixture 350g unchanged, and the rest is the same as Example 1 to prepare a geopolymer.
[0047] Example 4 This example adopts the same process as Example 1, except that, in this example, the mass ratio of kaolin to slag is 80:20 while keeping the total amount of admixture 350g unchanged, and the rest is the same as Example 1 to prepare a geopolymer.
[0048] Example 5 This example adopts the same process as Example 1, except that, in this example, the mass ratio of kaolin to slag is 75:25 while keeping the total amount of admixture 350g unchanged, and the rest is the same as Example 1 to prepare a geopolymer.
[0049] Example 6 This example adopts the same process as Example 1, except that, in this example, the mass ratio of kaolin to slag is 70:30 while keeping the total amount of admixture 350g unchanged, and the rest is the same as Example 1 to prepare a geopolymer.
[0050] Example 7 This example adopts the same process as Example 6, except that, under the condition that the total amount of water added remains unchanged, the amount of water in step (1) is adjusted to 73.14 g, and the amount of water in step (2) is adjusted to 71.68 g, so that the mass ratio of the composite foaming agent to water during the foaming process is 1:23. The rest is the same as Example 6, and a geopolymer is prepared.
[0051] Example 8 This example adopts the same process as Example 6, except that the foaming agent Enlin 12# is replaced with foaming agent 1 of equal mass, and the rest is the same as Example 6 to prepare a geopolymer.
[0052] Comparative Example 1 This comparative example is carried out in the same process as Example 6, except that: in this comparative example, while keeping the total amount of 3.18g of the composite foaming agent unchanged, the mass ratio of the foaming agent Enlin 12#, sodium dodecyl sulfate and sodium dodecyl sulfonate is 10:4:1, and the rest is the same as Example 6 to prepare a geopolymer.
[0053] Comparative Example 2 This comparative example is carried out in the same process as Example 6, except that: in this comparative example, while keeping the total amount of 384g of cementitious material unchanged, the total amount of alkali activator is adjusted to 24g (modulus is 1.1), and the total amount of admixture is adjusted to 360g, so that the mass ratio of alkali activator to admixture is 1:15, and the rest is the same as Example 6 to prepare a geopolymer.
[0054] Comparative Example 3 This comparative example adopts the same process as Example 6, except that: in this comparative example, while keeping the amount of 34g of the alkali activator unchanged, the amount of potassium silicate and potassium hydroxide is adjusted so that the modulus of the alkali activator is 1.3, and the rest is the same as Example 6 to obtain a geopolymer.
[0055] Comparative Example 4 This comparative example adopts the same process as Example 6, except that the foaming agent Enlin 12# is replaced by foaming agent 2, and the rest is the same as Example 6 to prepare a geopolymer.
[0056] Test Example 1 The geopolymer prepared in Example 6 was subjected to a scanning electron microscope test under the following test conditions: the test was conducted at an accelerating voltage of 10 kV and a working distance of 8 mm, and the surface morphology was observed using a secondary electron image (SEI) mode; The geopolymer prepared in Example 6 was subjected to CT scanning test, and the test conditions were: scanning resolution 22 microns, scanning time 3 hours, scanning angle 0° to 180°; Test results see Figure 1 and Figure 2 As shown. Among them, Figure 1 (a) is a 50x scanning electron microscope image. Figure 1 (b) shows a 300-fold scanning electron microscope image; it can be seen from the figure that the prepared geopolymer has a nano-micron-millimeter multi-level pore structure, and the individual pores are not connected, which synergistically inhibits molecular heat conduction, convection and radiation heat transfer, and the complex pore network greatly extends the heat transfer path; the low thermal conductivity of the enclosed gas (such as air) in the pores further reduces the overall thermal conductivity of the material. This multi-mechanism synergy gives it excellent thermal insulation performance, which is suitable for high-efficiency insulation scenarios such as building energy conservation.
[0057] Depend on Figure 2 It can be seen that the prepared geopolymer has a high porosity, and the high porosity increases the thermal resistance through the solid-gas interface, thereby achieving the purpose of thermal insulation.
[0058] Test Example 2 The thermal conductivity and thermal conductivity coefficient of the geopolymers prepared in the examples and comparative examples were determined, and the test method was based on GB / T10295-2008; the compressive strength of the geopolymers prepared in the examples and comparative examples was determined, and the test method was based on GB 17671-1999; the dry density of the geopolymers prepared in the examples and comparative examples was determined, and the test method was based on GB / T 11969-2020; the specific results are shown in Table 1.
[0059] Table 1
[0060] From the above content, it can be seen that the geopolymer of the present invention obviously has the characteristics of better thermal insulation, mechanical strength and light weight.
[0061] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A geopolymer composition, characterized in that: The composition contains a composite foaming agent, a gelling material and water in a mass ratio of 1:110-250:40-50; The composite foaming agent contains a foaming agent, sodium dodecyl sulfate and sodium dodecyl sulfonate in a mass ratio of 10:0.5-2:0.5-2; the pH value of the foaming agent is ≥8; the gelling material contains an alkali activator and an admixture in a mass ratio of 1:10-13; The modulus of the alkali activator is 1-1.2; and the admixture contains metakaolin and slag.
2. The composition according to claim 1, characterized in that The alkali activator is a combination of potassium silicate and potassium hydroxide.
3. The composition according to claim 1 or 2, characterized in that The metakaolin accounts for 70-95% of the total mass of the admixture, and the slag accounts for 5-30% of the total mass of the admixture.
4. The composition according to claim 1 or 2, characterized in that The admixture is a combination of metakaolin and slag.
5. A method for preparing a geopolymer, characterized in that: The method is carried out using the geopolymer composition according to any one of claims 1 to 4, and the method comprises: (1) subjecting a composite foaming agent to foaming treatment with water to obtain foam; and, The gelling material and water are first mixed to obtain a solution 1; (2) The foam and the solution 1 are mixed for a second time to obtain the geopolymer.
6. The method according to claim 5, characterized in that In the foaming process of step (1), the mass ratio of the composite foaming agent to the water is 1:10-20.
7. The method according to claim 5 or 6, characterized in that: In step (1), the foaming treatment operation includes: the foaming temperature is 30-40°C and the time is 2-5 minutes.
8. The method according to claim 5 or 6, characterized in that: The first mixing and the second mixing each independently meet the following conditions: temperature is 20-40° C., time is 2-30 min, and stirring speed is 500-1000 rpm.
9. The method according to claim 5 or 6, characterized in that: The method comprises: subjecting the product obtained by the mixing process to injection molding and curing treatment in sequence to obtain the geopolymer.
10. A geopolymer, characterized in that: The geopolymer is prepared by the method described in any one of claims 5-9.
Citation Information
Patent Citations
Basic group geopolymer porous material
CN102603355A
Mineral polymer foaming material as well as preparation method and application of mineral polymer foaming material
CN102617106A
Raw material composition of lightweight heat-insulating wall material, lightweight heat-insulating wall material, and preparation method of lightweight heat-insulating wall material
CN113372091A
Geopolymer foam adsorption material with pulse-shaped multi-stage network pore structure and preparation method of geopolymer foam adsorption material
CN116618014A
Three-phase foaming agent, alkali-activated foam concrete and preparation method
CN117902850A
Cited By
Composite material with fireproof and sound-proof functions, preparation method and application of composite material and fireproof and sound-proof door
CN122145090A